2016
DOI: 10.1136/sextrans-2015-052502
|View full text |Cite
|
Sign up to set email alerts
|

Saliva use as a lubricant for anal sex is a risk factor for rectal gonorrhoea among men who have sex with men, a new public health message: a cross-sectional survey

Abstract: Saliva use as a lubricant for anal sex is a common sexual practice in MSM, and it may play an important role in gonorrhoea transmission. Almost half of rectal gonorrhoea cases may be eliminated if MSM stopped using partner's saliva for anal sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 18 publications
3
45
0
1
Order By: Relevance
“…In addition, a substantial proportion of MSM (69%) use the partner's saliva as a lubricant for anal sex (6), suggesting that this might account for rectal gonorrheal infections in men who report condom use with receptive anal sex. This hypothesis is supported by a recent observational study showing that, after adjusting for potential confounders, including condom use for receptive anal sex, about 41% of the cases of rectal gonorrhea can be attributed to the use of a partner's saliva as a lubricant for anal sex (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a substantial proportion of MSM (69%) use the partner's saliva as a lubricant for anal sex (6), suggesting that this might account for rectal gonorrheal infections in men who report condom use with receptive anal sex. This hypothesis is supported by a recent observational study showing that, after adjusting for potential confounders, including condom use for receptive anal sex, about 41% of the cases of rectal gonorrhea can be attributed to the use of a partner's saliva as a lubricant for anal sex (6).…”
Section: Discussionmentioning
confidence: 99%
“…Given that a substantial gonococcal bacterial DNA load is present in saliva, it is plausible that gonorrhea can be transmitted through saliva across all three anatomical sites, that is, from the pharynx to the rectum via rimming (19), from the rectum to the pharynx via rimming (7), from pharynx to pharynx via wet kissing (7), from the pharynx to the urethra via oral sex (19), and/or via saliva use as a lubricant for masturbation (6). In addition, a substantial proportion of MSM (69%) use the partner's saliva as a lubricant for anal sex (6), suggesting that this might account for rectal gonorrheal infections in men who report condom use with receptive anal sex. This hypothesis is supported by a recent observational study showing that, after adjusting for potential confounders, including condom use for receptive anal sex, about 41% of the cases of rectal gonorrhea can be attributed to the use of a partner's saliva as a lubricant for anal sex (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…454 Early work has shown that antibacterial 1880 mouthwash might inhibit N. gonorrhoeae growth and studies of mouthwash for gonorrhoea 1881 prevention are underway. 439 We call on policy makers to fund research to better understand …”
mentioning
confidence: 99%
“…Most pharyngeal N. gonorrhoeae infections will remain undetected unless NAAT is used. Further, recent studies have reported that undetected pharyngeal gonorrhea can increase the risk of anal infection when saliva is used as a lubricant for anal sex (21).…”
Section: Discussionmentioning
confidence: 99%